Neutralization of acidic soil using Myxococcus xanthus: Important parameters and their implications. Issue 4 (4th July 2021) - Cho, MinJung; Park, SeonYeong; You, EunYoung; Kim, ChangGyun
ABSTRACT: Soil acidification through acid rain/deposition has been a serious problem that adversely affects the soil environment. In this study, Myxococcus xanthus, myxobacteria, was assessed towards neutralization of artificial acidic soil. Differences in initial pH and peat moss content in soil with incubated M. xanthus were being compared using a one-variable-at-a-time approach. It showed that the M. xanthus could neutralize the acidified soil using their specific metabolism, producing ammonium ions and hydroxide simultaneously. Increasing peat moss content could direct the neutralization performance of M. xanthus towards inhibition whereas reducing the peat moss content could improve the neutralization performance. Among experimental parameters such as initial pH, peat moss content in soil, and microorganism concentration, the interaction of soil amount either with peat moss content or microbial population density was meaningfully correlated to the neutralization of acidic soil.